Metallothionein II treatment mitigates rotenone-induced neurodegeneration in zebrafish models of Parkinson’s disease - Nies, Yong Hui; Lim, Wei Ling; Abd Karim, Norwahidah; Yahaya, Mohamad Fairuz; Teoh, Seong Lin (Frontiers in Pharmacology, 2025)
IntroductionParkinson’s disease (PD) is a common neurodegenerative disorder primarily affecting motor function due to progressive loss of dopaminergic neurons in the substantia nigra. Current therapies offer symptomatic relief but fail to halt disease progression, highlighting the need for novel therapeutic strategies. This study explores the neuroprotective potential of exogenous human metallothionein 2 (hMT2) peptide in a rotenone-induced PD zebrafish model.MethodsAdult zebrafish were divided into four groups: control, rotenone-treated, hMT2 pre-treatment, and hMT2 co-treatment. PD model was established by exposing zebrafish to 5 µg/L rotenone water for 28 days. hMT2 (0.2 µg) was administered intracranially either one day before or seven days after rotenone exposure.ResultsThe novel tank test demonstrated that rotenone exposure significantly impaired locomotor activity (p < 0.05) and increased anxiety-like behavior (p < 0.001). Additionally, PD model zebrafish exhibited reduced dopamine levels, decreased dopaminergic neuron population, elevated oxidative stress, heightened inflammatory response and mitochondrial dysfunction. Treatment with hMT2, especially in the co-treatment group, ameliorated these deficits by restoring locomotor activity, dopamine levels, and dopaminergic neuron counts while reducing oxidative stress and inflammation, and improving mitochondrial function.DiscussionThese results suggest that hMT2 exhibited neuroprotective effect in the PD model zebrafish. These findings support the potential of MT as a therapeutic agent for PD.